2020
DOI: 10.1097/md.0000000000019017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of 18F-FET PET/CT in newly diagnosed WHO 2016 high-grade glioma

Abstract: O-(2-[18F]fluoroethyl)-l-tyrosine positron-emission tomography/computed tomography (18F-FET PET/CT) is well known in brain tumor management. Our study aimed to identify the prognostic value of 18F-FET PET/CT in high-grade gliomas (HGG) according the current 2016 World Health Organization (WHO) classification. Patients with histologically proven WHO 2016 HGG were prospectively included. A dynamic 18F-FET PET/CT was performed allowing to obtain 2 static PET frames (static frame 1: 20–40 minutes and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…21 Other publications suggested that FET PET/CT is a useful noninvasive tool for prognosis of brain tumors. [22][23][24] There was no false-positive case in our study for PSMA PET. However, there was 1 patient with grade III oligodendroglioma whose lesion did not show significant PSMA uptake (patient 8).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…21 Other publications suggested that FET PET/CT is a useful noninvasive tool for prognosis of brain tumors. [22][23][24] There was no false-positive case in our study for PSMA PET. However, there was 1 patient with grade III oligodendroglioma whose lesion did not show significant PSMA uptake (patient 8).…”
Section: Discussionmentioning
confidence: 98%
“…MET and O -(2-[ 18 F] fluoroethyl)-l-tyrosine FET PET are superior to FDG in terms of sensitivity for identifying glioma grade 21 . Other publications suggested that FET PET/CT is a useful noninvasive tool for prognosis of brain tumors 22–24 …”
Section: Discussionmentioning
confidence: 99%
“…The pathological differentiation based on the WHO classification system. 9 Forty-two pairs of gliomas and adjacent para-carcinoma tissue samples were collected between January 2018 and December 2019. These tissues were instantly placed into liquid nitrogen to protect RNA integrity and stored at −80°C for further analysis.…”
Section: Patient Tissue Samplesmentioning
confidence: 99%
“…Dynamic susceptibility contrast brain MRI evaluates several aspects of brain vasculature by assessing different parameters such as relative cerebral blood volume (rCBV) and permeability. It could provide additional information compared to conventional MRI [7] to allow a more robust characterization of the peritumoral area. Moreover, diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) maps illustrate restricted diffusion of water molecules in the cellular microenvironment [8].…”
Section: Introductionmentioning
confidence: 99%